2011
DOI: 10.1111/j.1399-3038.2011.01143.x
|View full text |Cite
|
Sign up to set email alerts
|

Training of trainers on epinephrine autoinjector use

Abstract: The majority of physicians do not know how to use epinephrine autoinjectors. This displays that current education of physicians on anaphylaxis is inadequate for a thorough practice. We hypothesize that a theoretical lecture together with a practical session on epinephrine autoinjector use will improve its proper use by physicians. Residents, specialists, and consultants from General Pediatrics excluding allergists and allergy fellows were included in this study. All physicians were given an eight-item question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 19 publications
4
43
0
Order By: Relevance
“…The results appear to support other reports in the literature [19]- [29] regarding the inadequacy of the current approach to adrenaline injection education (i.e., expert explanation and AAI demonstration). Current instruction, where the use of AAIs is just demonstrated does not include provision for feedback, nor encouragement nor support of continuous practice.…”
Section: Discussion Of Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The results appear to support other reports in the literature [19]- [29] regarding the inadequacy of the current approach to adrenaline injection education (i.e., expert explanation and AAI demonstration). Current instruction, where the use of AAIs is just demonstrated does not include provision for feedback, nor encouragement nor support of continuous practice.…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…The assessment of AAI performance was based on the four-step marking scheme used in other studies [19], [29], which, in turn, were based on the steps recommended by the EpiPen® AAI manufacturer [49] The AllergiSense system separates step 2 into two by i) sensing "swing and jab" and ii) explicitly asking the user to select the correct injection site from a randomly ordered list. In addition, AllergiSense senses for the injector being held the right way around.…”
Section: Assessment Of Performance and Administered Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical features (particularly the size) of the device influenced the decision of the others not to carry it consistently Money et al (2013) [27] The design of EAIs should receive attention as patients often fail to carry them owing to size and esthetics Simons et al (2010) [28] Unintentional injections from EAIs increased annually from 1994 to 2007, suggesting that improved EAI design is needed, along with increased vigilance in training the trainers and the users Arga et al (2011) [29] Ongoing mistakes in EAI use that occur despite integrated theoretical and practical education might be related to its design [30] Competence in using EAIs was associated with regular visits to the allergy clinic and decreased as time elapsed from first EAI instruction to the last visit, indicating that acquired skills are not permanent [31] Medical interns' competence with EAIs was maintained for the first 3 months after training but decreased by 6 months, suggesting that frequent regular retraining is needed Brown et al (2013) [32] Immediately after a one-to-one demonstration, 15% of mothers who had no experience with EAIs could not 'fire' an EAI device correctly, identifying a need for more user-friendly devices and training Chad et al (2013) [33] 56% (672 of 1209) of parents expressed fear about EAI use: specifically, fear of hurting the child, using the EAI incorrectly, or a bad outcome Schwirtz and Seeger (2010) [34] Data on mechanical stress and injection performance characteristics indicated significant limitations in the design and quality of the EAIs tested Auvi-Q-specific references…”
Section: Eai References Key Messagementioning
confidence: 99%
“…Guerlain et al (2010) [35] User-centred device design potentially has a significant impact on correct EAI use and patient preference [36] The sharps-injury-prevention feature was validated for the HFE-designed EAI, and healthcare professionals perceived the device to be a safer and preferred alternative to existing EAIs Camargo et al (2013) [37] Auvi-Q, an HFE-designed EAI with audio and visual cues, was preferred over EpiPen among experienced and inexperienced adults, caregivers and children Edwards et al (2013) [38] The Patient Information Leaflet and other labeling features were effectively communicated instructions for successful Auvi-Q use by untrained adults and children A study that aimed to reduce errors in EAI use by trainee allergists concluded that 'mistakes' in use that occurred despite intensive education were related to EAI design [29].…”
Section: Key Messagementioning
confidence: 99%